Colonic cancer in families without polyposis: enfoque clínico y anátomo-patológico. Perspectivas de estudio genético - Sarroca, Carlos; Acosta Ferreira, Walter; Quadrelli, Roberto (Cirugía del Uruguay, 1977)
The authors study a family suffering from cancer, predominantly of colon, although no polyps have been found in this organ. A group of brothers ,in the III generation are studied, 8 of whom have reached adulthood. Six of them were operated for 11 neoplasias, 8 of which were malign, and 7 of which were colonic cancers.